2008
DOI: 10.1007/s11999-008-0427-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Navigation Measurements of TKA Limb Alignment Do Not Correlate

Abstract: Precise pre-and postoperative anatomic measurements are necessary to plan, perform, and evaluate total knee arthroplasty (TKA). We evaluated the relationship between radiographic and navigation alignment measurements, identified sources of error in radiographic and navigated alignment assessment, and determined the differences between desired and clinically accepted alignment. Fifty-eight computer-assisted TKAs were performed and limb alignment measurements were recorded both pre-and postoperatively with stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 28 publications
9
73
2
Order By: Relevance
“…Our results were comparable to previous studies when evaluating cutting error [1,10,12,14] (Table 1), implanting error [9] (Table 2) and radiographic error [15,16] (Table 3). Our study is the first to evaluate all types of errors (cutting, implanting and radiographic error).…”
Section: Discussionsupporting
confidence: 90%
“…Our results were comparable to previous studies when evaluating cutting error [1,10,12,14] (Table 1), implanting error [9] (Table 2) and radiographic error [15,16] (Table 3). Our study is the first to evaluate all types of errors (cutting, implanting and radiographic error).…”
Section: Discussionsupporting
confidence: 90%
“…Patients with large intraarticular deformities might be easier to correct to neutral alignment than those with large degrees of varus in the tibia, potentially affecting outcome. Fifth, manual goniometer measurements of limb alignment reportedly are accurate to between 2°and 3° [7,29]. The use of digital radiography and computers for angle measurements might improve the accuracy of these measurements [26].…”
Section: Discussionmentioning
confidence: 99%
“…It could therefore be inferred that repeatable measurements are also accurate, as in order for measurements to be repeatable, soft tissue artefacts must be minimal. In addition, it could be argued that the acknowledged long-leg radiographic gold standard has more potential variation [14] than the IR system, and that disagreement between measurements may not reflect true inaccuracies [36]. Although several obese subjects were enrolled in the study, none were morbidly obese and no subject reported discomfort when performing the necessary kinematic maneuvers.…”
Section: Discussionmentioning
confidence: 99%